(n,α) reaction cross sections of 44Ca, 45Sc, and 51V nuclei from 13.6 to 14.9 MeV - Subasi, M; Erduran, MN; Bostan, M; Reyhancan, IA; Gultekin, E; Tarcan, G; Ozbir, Y; Durusoy, A (AMER NUCLEAR SOCIETY, 1998)
Cross sections were measured for the Ca-44(n, alpha)Ar-41, Sc-45(n, alpha)K-42, and V-51(n, alpha)Sc-48 reactions at neutron energies from 13.6 to 14.9 MeV. The neutrons were produced via the H-3(d, n)He-4 reaction on a neutron generator using a solid TiT target. The activation technique was used, and induced gamma activities were measured by a high-resolution gamma-ray spectrometer. Corrections were made for the effects of gamma-ray attenuation, random coincidence (pulse pileup), coincidence summing, dead time, neutron flux fluctuations, and low-energy neutrons. Statistical model calculations taking into account precompound effects were performed for all the reactions investigated, and the experimental results were reproduced well except for the (n, alpha) reaction on the Sc-45 target. Also, comparisons with the recent experimental data showed good agreement.
Keywords: NEUTRON; ENERGY; Nuclear Science & Technology